Toward a more amicable Asia-Pacific region Japan's roles - Sugita, Yoneyuki (University Press of America, 2016)
The Asia-Pacific region has been enjoying fast growing economy. As President Barack Obama's "pivot to Asia" strategy indicates, this region is an engine for the world economic growth.